2016
DOI: 10.3389/fpsyg.2016.01307
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Procrastination: Comparing Two Scales in Six European Countries

Abstract: Procrastination is a common problem, but defining and measuring it has been subject to some debate. This paper summarizes results from students and employees (N = 2893) in Finland, Germany, Italy, Norway, Poland, and Sweden using the Pure Procrastination Scale (PPS) and the Irrational Procrastination Scale (IPS; Steel, 2010), both assumed to measure unidimensional and closely related constructs. Confirmatory factor analyses indicated inadequate configural fit for the suggested one-factor model for PPS; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 53 publications
26
80
1
Order By: Relevance
“…2 In the next iteration of modification indices analysis, a path from PPS factor implemental delay and item 9 was suggested. This item (“I find myself running out of time”) has previously been argued to be conflated with the busyness construct and not procrastination per se ( Steel, 2010 ; Svartdal et al, 2016 ) and recommended for deletion from procrastination scales. Deleting it improved overall fit, RMSEA = 0.062, CFI = 0.974, SRMS = 0.028.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 In the next iteration of modification indices analysis, a path from PPS factor implemental delay and item 9 was suggested. This item (“I find myself running out of time”) has previously been argued to be conflated with the busyness construct and not procrastination per se ( Steel, 2010 ; Svartdal et al, 2016 ) and recommended for deletion from procrastination scales. Deleting it improved overall fit, RMSEA = 0.062, CFI = 0.974, SRMS = 0.028.…”
Section: Resultsmentioning
confidence: 99%
“…As for the IPS, this scale attempts to measure a single construct, “irrational delay” ( Steel, 2010 ). Research has subsequently confirmed this (e.g., Svartdal et al, 2016 ), although the three reversed items of the scale (items 2, 6, and 9) seem to measure the construct somewhat less optimally compared to the others and have even been suggested to load on a different factor ( Rozental et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is observed that the mean APS score is highest for the age group less than 20 and second highest for the age group 21 -25. Svartdal et al [13] and Steel & Ferrari [14] observed that as age increases, the level of procrastination decreases. Similar, results were observed in the current study as well, which showed that age and overall APS scores are negatively correlated to each other, which implies that as age increases procrastination decreases.…”
Section: Agementioning
confidence: 99%